(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the development of olive oil production and consumption in Libya during the period 1980–2024, assessing the food gap and self-sufficiency ratio, and identifying the main influencing factors. A quantitative and descriptive analytical approach was adopted using official annual data. Linear regression models were applied to estimate general trends, in addition to calculating the compound annual growth rate and the self-sufficiency ratio. The findings indicate significant fluctuations in domestic production, ranging from 4,360 tons in low-production years to 19,620 tons in recent years. Consumption remained relatively stable with slight variations, leading to a persistent but declining food gap. Trend equations revealed a positive annual increase in production and a negative trend in consumption, resulting in a gradual reduction of the food gap. The compound annual growth rate showed a 1.86% annual increase in production, a −1.15% decrease in consumption, and a −4.87% annual decline in the gap, reflecting improved production capacity and higher self-sufficiency levels. The study recommends enhancing agricultural technologies, improving olive varieties, strengthening extension services, and supporting marketing policies to promote sector sustainability and reduce reliance on imports.